The Role Of Monitoring And Control Systems In The Performance Of Commercial Banks In Kenya (Cuea Journal of Business and Economics, 2025)
This study reviewed how monitoring and control systems affected the performance of commercial banks in Kenya between 2020 and 2025, a time when returns to investments varied, market shares shifted, levels of client satisfaction were varying, and credit risk was on the rise. The Control Theory guided the investigation as it highlights the significance of feedback and regulation in organizational performance. The research design included a descriptive cross-sectional study that gathered data through structured questionnaires across the 38 licensed commercial banks in Kenya (represented by Heads of Operations Departments and Strategy Managers). The SPSS Version 28 was used to conduct data analysis, and the instrument reliability was validated with a pilot study, where Cronbach’s Alpha coefficients were above 0.7. Diagnostic tests confirmed that the data passed critical regression analysis assumptions such as normality, no multicollinearity (VIF < 2), and no homoscedasticity. The regression model showed that the variations in bank performance could be strongly attributed to monitoring and control systems with R-squared at 0.837 and adjusted R-squared being 0.828. The results demonstrate that effective monitoring and control systems are a significant factor in promoting operational efficiency, competitiveness, and consumer satisfaction among Kenyan commercial banks. Such lessons offer beneficial advice to bank managers, policymakers, and change managers who seek to sustain performance in an evolving financial context. In the study, ethical considerations such as informed consent, confidentiality, and voluntary participation were strictly upheld.